Evolution of sport wearable global navigation satellite systems` receivers: A look at the Garmin Forerunner series - Szot, T. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2026)
Global Navigation Satellite Systems (GNSSs) have revolutionised many areas of human life by providing location, navigation, tracking, mapping and timing capabilities. The use of this technology would not be possible without receivers designed for specific applications. One of these areas is sport. The article discusses the advancements made in wearable sport devices over the past two decades (2003-2023) and uses Garmin`s Forerunner receivers as an example. Nineteen of the most advanced models were analysed chronologically and reviewed in three sections: physical properties, internal and external sensors and other functional aspects. The lists are preceded by a description of the historical background of the technology, an explanation of the general principles of operation and the identification of ground-breaking mobile devices before the year 2003. The summary identifies the most likely changes that will affect the publicly available, wearable sports GNSS receivers in the near future.